Development of Cognitive Abilities of Preschool Children with the Help of Nature - Tursunoy Buriyeva (Genius Journals, 2022)
Nature is an inexhaustible source of development of intellectual abilities of children, spiritual enrichment, and education of their comprehensively developed personality. Communication with nature helps to form in children real knowledge about the world around us and a human attitude towards living beings. This article discusses the role and importance of acquaintance with nature in the formation of the cognitive abilities of preschool children
Keywords: nature; knowledge; intuition; emotional knowledge